The spiral progression approach in teaching science: Its Volatilities, Uncertainties, Complexities, and Ambiguities (VUCA) - Jomarie V. Baron; Jaycob A. Dela Cruz (Journal of Social, Humanity, and Education, 2023)
Purpose: The purpose of the study is to assess the implementation of the spiral progression approach in teaching science according to the threat of its volatility, uncertainty, complexity, and ambiguity (vuca).  Methodology of Research: Descriptive research design was employed in this study, and the total enumeration technique was used to determine the respondents. A valid and reliable self-made questionnaire was utilized in the conduct of the study. Results: As viewed in the result of the study, it was found that the VUCA level of the spiral progression approach in teaching science is Low, therefore there is a minimal threat and issues that need to be addressed properly since if ignored, it will pose a bigger problem in the future. Likewise, the implementation of the spiral progression approach in science teaching is geared toward the right track. Limitations: This study looks into the implementation of the spiral progression approach and assesses its volatilities, uncertainties, complexities, and ambiguities (VUCA) as a way to cope with its complex conditions as perceived by science teachers and serves as variables of the study. Respondents of the study were limited only to those teachers teaching secondary science in the school year 2021-2022. Contribution: This research endeavor will be beneficial as it aims to add knowledge on the implementation of the Spiral Progression Approach with a special focus on its volatility, uncertainty, complexity, and ambiguity which will become the basis of future programs and policies to illuminate the current set of understanding about this educational reform program.